Surface porosity enhancement of activated carbon by synthesizing kenaf fiber - Zulaikha, S.N.; Kadoura, Ahmed Mohamed; Alkbir, M.F.M.; Mohammad, Zulhaimi; Kosnan, Shahrul Effendy; Januddi, Fatihhi (Ismail Saritas, 2024)
Kenaf is one type of natural fibre (KF) that has been applied in a variety of industrial settings. Scientists, engineers, and researchers have recently become interested in natural fiber as a substitute component to improve the efficiency of the adsorption method. It is thought that using kenaf as an adsorbent is a creative and appealing technique. As a result, it has been applied to many different adsorption tasks. Kenaf fibre has high specific strength, is an inexpensive resource, is environmentally friendly, and has strong structural stiffness, making it suitable for a wide range of applications. Previous research concentrated on the effects of various activated carbon types on the distribution of pore volumes. The research also demonstrated the excellent performance of two distinct elements: kenaf fibre and activated carbon (AC) derived from bone char. Because of its many advantageous qualities, including its porous structure, ease of use, affordability, and ability to function well in a variety of temperatures and humidity conditions, kenaf fiber can be a useful addition to activated carbon to increase its porosity. Additionally, the overall characteristics of synthesized activated carbon (SAC) are influenced by the values of the fixed carbon determination, bulk density, pore volume, moisture content, and ash content. The degree of porosity alteration of the SAC will be determined by synthesizing AC with KF to promote the expansion of surface porosity and pore volume. The analysis from Water Quality Standards: Physical Benchmark could be used to determine SAC's performance.